Understanding police use of force : officers, suspects, and reciprocity - Alpert, Geoffrey P.; Dunham, Roger G.; Cambridge eBooks (Cambridge : Cambridge University Press, 2004)
Whenever police officers come into contact with citizens there is a chance that the encounter will digress to one in which force is used on a suspect. Fortunately, most police activities do not involve the use of force. But those that do reflect important patterns of interaction between the officer and the citizen. This book examines those patterns. It begins with a brief survey of prior research, and then goes on to present data and findings. Among the data are the force factor applied - that is, the level of force used relative to suspect resistance - and data on the sequential order of incidents of force. The authors also examine police use of force from the suspect's perspective. In analyzing this data they put forward a conceptual framework, the Authority Maintenance Theory, for examining and assessing police use of force.
Introduction : the context of police use of force -- Police use of force : the history of research -- The crucial element : finding research sites -- Findings from Miami-Dade Police Department study -- The sequential steps in use-of-force incidents in the Miami-Dade Police Department -- Miami-Dade Police Department : inconsistencies between officer and suspect accounts of the use of force -- Findings from Prince George's County Police Department -- Findings and summary -- Explaining police use of force : the breakdown of an authority maintenance ritual.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Arrest (Police methods); Restraint of prisoners -- United States; Police brutality -- United States; Police discretion -- United States; Electronic books